Fermented and unfermented palm kernel cake as broiler chicken - Ketaren, P.P; Sinurat, A.P; Zainuddin, D; Purwadaria, T; Kompiang, I.P (Indonesian Animal Sciences Society, 1999)
feed. Two hundred and ten, day-old broiler chicks were used for this study. They were allotted to 6 different diets containing either BIS or FBIS at 3 different levels (5, 10 and 15%) and one control diet. The results showed that 5% BIS and 5% FBIS could be used in broiler diet without adversely affecting feed intake, weight gain and feed conversion ratio. FCR of those diets were significantly (P<0.05) better than the control diet. Carcass yields were not significantly affected by feeding of BIS nor FBIS. The FBIS diet produced less abdominal fat than the BIS diet. Â Key words : Palm kernel cake, fermentation, broilers